AB1219 Outcome of pediatric patients with end stage renal disease secondary to systemic lupus erythematosus in croatia in the last four decades. (23rd January 2014) - Mustapic, Ž.; Puretic, Z.; Slavicek, J.; Frkovic, M.; Jelusic, M.
Abstract : Objectives: to evaluate outcome of pediatric patients with end stage renal disease (ESRD) due to lupus nephritis and to determine has intensive specific treatment in SLE decreased incidence of ESRD and need for renal replacement therapy (RRT), dialysis and kidney transplantation, in pediatric patients in the last four decades in Croatia. Methods: we evaluated basic data from national registry of pediatric patients (under the age of 18 years) receiving renal replacement therapy for ESRDin a period of 1972-2011. Data were collected from three major tertiary clinical centers performing RRT in pediatric patients. Results: Since 1972, 156 children, 96 boys (61%) and 70 girls (39%), received RRT for ESRD. Seven of them, 3 girls and 4 boys, secondary to SLE (4%). Median age in these children when RRT was initiated was 15 years. 6 children started with hemodialysis in 1972-2002, and two of them died while waiting for kidney transplantation. Since 2002, only one child needed RRT (peritoneal dialysis) and has been succesfuly transplanted. At the same period of time, 27 children with SLE was treated with plasmapheresis, and only 2 of them in the last 10 years. Conclusions: Our findings indicate that change in initial therapies improved outcome of children with SLE as well as need for dialysis or kidney transplantation in recent years. We also found that therapeutic plasmapheresis is used significantly less frequent probablydue to increased availability of powerful immunosuppressive drugs such as mycophenolate mofetil and azathioprine. Disclosure of Interest: None Declared